Numerical simulations of subduction zones Effect of slab dehydration on the mantle wedge dynamics - Arcay, D; Tric, E; Doin, M-P (Physics of the earth and planetary interiors, 2005)
In oceanic subduction zones, dehydration of slab's minerals may favor asthenospheric flow in the mantle wedge by decreasing rocks strength. This should enhance the upper plate base reheating and markedly alter its thermal structure. To quantify this phenomenon, we model slab subduction within a viscous mantle, dehydration-hydration processes, and the rock strength dependence on water content. We use accurate phase diagrams for a H sub(2)O- satured mantle peridotite and a gabbroic crust to determine at each time step the amount of water released or absorbed by each unit of rock. Transition phases are supposed to be not metastable. Water is released from the oceanic crust and from the altered peridotite portion of the slab. Dehydration of the subducting lithosphere occurs first at 60-75 km depth, when the crust is eclogitized, and second, deeper around 105 km when serpentine and chlorite in serpentinite layer below the crust become unstable. For high convergence rates, because of cold, P,-, T,-, t, paths in the slab, serpentine can be transformed into the hydrated phase A and water is recycled by the slab until great depth. However, in all investigated cases, the released water is sufficient to hydrate by dissolution the whole mantle wedge until, 217 plus or minus 55, km away from the trench and, as it goes up, to form hydrated minerals in the overlying lithosphere over a significant volume. The convergence rate slightly shifts dehydration fronts location, and consequently widens or reduces the hydrated mantle wedge. Note that for the dynamic corner flow modelled here, with a non- Newtonian rheology, the slab surface is significantly warmer than for an isoviscous analytical corner flow model, yielding plausible crust melting. We assume a strength reduction associated to hydration larger for rocks containing nominally hydrous minerals than for rocks with only dissolved water. The rock strength thus becomes quite uniform at the base of the hydrated upper plate and in the wedge. This results in cooler temperatures along the slab top, but in an enhanced corner flow effect on the upper plate thermal structure. For large hydration strength reductions, a strong thermal erosion of the overlapping lithosphere develops in less than 15 Myr due to convective destabilization. This weakens drastically the upper plate at a distance from 110 to 220 km away from the trench. The geometry of the eroded region could correspond to the low- velocity zone observed below the arc region.